The Influence of Using Website-Based Learning Media (Math-Learning) on Students' Cognitive Learning Outcomes - Dwiana Ni'matus Salihah (Universitas Kanjuruhan Malang, 2022)
The purpose of this study is to describe and test the implementation and influence of the use of website-based defense media on the cognitive learning outcomes of 3rd-grade students at SDN Bakalan Krajan 1, Malang City. This study uses a quasi-experimental design with a nonequivalent control group design model. Data is collected quantitatively using test instruments and analyzed using t-tests assisted by SPSS 23 software. The results showed that the implementation of learning using website-based media in class 3C got a success percentage of 90.4% with excellent criteria. Furthermore, data analysis using different tests (t-test) found that the experimental class got a value of t = 3.75 with a significance level of 0.001 (p<0.05), and the control class got a value of t = 1,02 with a significance level of 0.320 (p>0.05). From these results, it can be concluded that learning using website-based media influences the cognitive learning outcomes of 3C grade students at SDN Bakalan Krajan 1, Malang City. Therefore, it is expected that research related to this can be used by the department, principal, and teachers as material to be socialized and applied to the learning of elementary students.